Designing Solar Power Plants as a Source of Electricity for Insect Traps - Misbahul Munir; Royb Fatkhur Rizal; Yoppy Egitanio (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
This study proposes the design and evaluation of a solar-powered insect trapping system as an environmentally friendly solution for pest control in agricultural fields. The system integrates a photovoltaic (PV) module as the primary energy source with a microcontroller-based control unit. A Passive Infrared (PIR) sensor is employed to detect insect movement, while an electric grid mechanism is used for pest eradication. The system is controlled using an Arduino microcontroller to ensure synchronized operation between detection and execution components. The research methodology involves system design, hardware and software implementation, and field testing in rice cultivation areas. Experimental results indicate that the device provides an effective illumination radius of approximately 5 meters and successfully captured 87 insect pests within two days of operation. Furthermore, the system demonstrates stable energy performance, with efficient battery charging during the daytime and reliable operation at night. These findings confirm that the proposed solar-powered insect trap is a viable, sustainable, and eco-friendly alternative to conventional pesticide-based pest control methods. Future work will focus on optimizing light intensity, improving sensor accuracy, and integrating ultraviolet light to enhance insect attraction.